Reduced Medication in Organic Farming with Emphasis on Organic Dairy Production - Bennedsgaard Torben W; Vaarst Mette (Acta Veterinaria Scandinavica, 2002)
Medication is an important focus area in organic animal husbandry. The combination of goals relating to improved animal welfare and reduced use of chemicals in general creates a common wish to reduce medication. Based on data from current Danish research projects in organic dairy farming, one specific organic medication pattern or policy cannot be described. The disease treatment pattern is influenced by many factors, e.g. the interaction with colleagues, veterinarians and agricultural advisors. No significant difference could be found with regard to incidence of mastitis treatments or somatic cell counts in 27 organic and 57 conventional herds. A marked tendency to shorter treatment periods in relation to mastitis treatments was described for organic farms in comparison with conventional farms (1.9 days versus 3.2 days (5 organic and 7 conventional herds)). In a study of development of health advisory service in organic herds, the dialogue between farmer, veterinarian and agricultural cattle advisor changed the treatment pattern markedly during a period of 6 months. Among important future challenges for veterinarians in organic farming is pointed at the constructive, open, and critical interaction with the single organic farmer as well as the organic animal husbandry system in general.